The Effectiveness of Learning Activities in Pronouncing the English Vowel Schwa by EFL College Level Students - Dala Munther Faraj (Zanco Journal of Humanity Sciences)
Pronunciation is an important element in learning English. One can achieve a good understanding from others by mastering the correct use of the sounds. In this research, the researcher emphasizes the role of pronouncing schwa vowel properly. Most English language learners face difficulties in pronouncing the vowel schwa. Thus, the researcher aims to address this problem.